Genome-Wide Identification and Analysis of Enhancer-Regulated microRNAs Across 31 Human Cancers - Tang, Fei; Zhang, Yin; Huang, Qing-Qing; Qian, Ming-Ming; Li, Zhi-Xue; Li, Yan-Jing; Li, Bei-Ping; Qiu, Zheng-Liang; Yue, Jun-Jie; Guo, Zhi-Yun (Frontiers in Genetics, 2020)
Enhancers are cis-regulatory DNA elements that positively regulate the transcription of target genes in a tissue-specific manner, and dysregulation of target genes could lead to various diseases, such as cancer. Recent studies have shown that enhancers can regulate microRNAs (miRNAs) and participate in their biological synthesis. However, the network of enhancer-regulated miRNAs across multiple cancers is still unclear. Here, a total of 2,418 proximal enhancer–miRNA interactions and 1,280 distal enhancer–miRNA interactions were identified through the integration of genomic distance, co-expression, and 3D genome data in 31 cancers. The results showed that both proximal and distal interactions exhibited a significant cancer type-specific feature trend at the tissue level rather than at the single-cell level, and there was a noteworthy positive correlation between the expression of the miRNA and the number of enhancers regulating the same miRNA in most cancers. Furthermore, we found that there was a high correlation between the formation of enhancer–miRNA pairs and the expression of enhancer RNAs (eRNAs) whether in distal or proximal regulation. The characteristics analysis showed that miRes (enhancers that regulated miRNAs) and non-miRes presented significant differences in sequence conservation, guanine–cytosine (GC) content, and histone modification signatures. Notably, GC content, H3K4me1, and H3K36me3 were present differently between distal and proximal regulation, suggesting that they might participate in chromosome looping of enhancer–miRNA interactions. Finally, we introduced a case study, enhancer: chr1:1186391–1186507 ∼ miR-200a was highly relevant to the survival of thyroid cancer patients and a cis-eQTL SNP on the enhancer affected the expression of the TNFRSF18 gene as a tumor suppressor.